PROFESSIONALISM OF ISLAMIC RELIGIOUS EDUCATION TEACHERS ON STUDENT CHARACTER AT SDN CIKUJANG - Ajat Saputra; Indri Yulianti, Ira Rahmayanti, N. Syaadiah (International Journal of Teaching and Learning, 2024)
Professional teachers are people who have special abilities and expertise in the field of teaching so that they are able to carry out their duties and functions as teachers with maximum ability, people who are well educated and trained, and have experience in the field. This research is motivated by the development of the world of education which requires professional human resources and also smart and character resources as an effort to shape student character. This research uses a qualitative method. This research uses data collection techniques by means of observation, interviews, and documentation. The results of the research conducted at SDN Cikujang show that the professionalism of Islamic religious education teachers towards student character at SDN Cikujang is carried out by providing examples, carrying out religious habituation activities and Islamic exemplary stories.